Characterization by X-ray powder diffraction of alpha lipoic acid. Issue 1 (28th November 2016) - Quintana Mendoza, Jose H.; Toro, R. A.; Blanco, Laura A.; Henao, J. A.
Abstract : Alpha lipoic acid (ALA) C8 H14 O2 S2 is a naturally occurring compound that is synthesized in small amounts by plants and animals, including humans. ALA is covalently bound to specific proteins, which function as cofactors for several important mitochondrial enzyme complexes and studies suggest that they might help with type 2 diabetes. In the Cambridge Structural Database, there are four entries related to this compound: two for lipoic acid and two for complexes. In the Powder Diffraction File-4, two experimental unindexed patterns are reported. The material crystallizes in a monoclinic crystal system, space group P 21 / a and cell parameters a = 9.237 (1) Å, b = 9.960 (1) Å, c = 11.787 (2) Å, β = 109.13 (1)°, and V = 1024.6 (2) Å 3 .